Role of histone regulations and modifications in cognitive functions of mitragynine (a major indole alkaloid of mitragyna speciosa) - Radhakrishnan, Sonia Dhiya (2021)
Introduction: Previous researchers reveal that drug addiction does alter cognitive mechanisms in humans and bring changes to cognitive behaviour. Experimental studies involving addiction of drugs like heroin, cocaine and many others have shown to have impact on memory and learning capabilities which results in cognitive decline. This condition can worsen if drug is constantly consumed in long run and high doses. In this study, we were looking at mitragynine, a main compound of Mitragyna speciosa, affects cognitive abilities and the changes of histone protein in the brain. Currently, there is no research that has been done to correlate mitragynine and epigenetics. Objective: This study primarily aims to investigate the cognitive function and histone modifications in the mitragynine treated rats. Methodology: Behavioural task was conducted in mitragynine-treated rats to analyse the memory and learning functions caused by different doses of mitragynine (1, 10 and 30mg/kg) at different time frames. Passive avoidance task (PAT) and western blot (WB) protocol were used for cognitive behavioural study and protein analysis, respectively. Results: This study highlighted significant results of cognitive impairment at 1 hour retention time, but not at 24 hours and 7 days in PAT with no changes of histone H3K9 protein expression Conclusion: Mitragynine caused cognitive impairment during early stages of drug metabolism in the rat’s body. This study concluded that mitragynine caused cognitive dysfunction with no changes of histone protein expression.